Pt(II) Complexes with Linear Diamines—Part I: Vibrational Study of Pt-Diaminopropane. Issue 5 (11th July 2012) - de Carvalho de Carvalho, Ana L. M. Batista Ana L. M. Batista; Fiuza Fiuza, Sónia M. Sónia M.; Tomkinson Tomkinson, John John; de Carvalho de Carvalho, Luís A. E. Batista Luís A. E. Batista; Marques Marques, M. Paula M. M. Paula M.
Abstract : A conformational analysis of the Pt(dap)Cl2 complex (dap = 1, 3 -diaminopropane) was performed by vibrational spectroscopy (FTIR, Raman, and INS), coupled to quantum mechanical methods within the density functional theory (DFT) and effective core potential (ECP) approaches. A complete spectral assignment of the system was achieved, due to the combined use of all available vibrational spectroscopic techniques. A good agreement was found between experimental and theoretical results, as well as with reported data for analogous complexes (e.g., cisplatin).